Analysis Of the Acceptance and Feasibility Of Semi-Technical Paddy Rice Farming Business In Tanjung Agung District, Muara Enim Regency - Benyu Khalalkand; Munajat, Munajat; Fifian Permatasari (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the Acceptance and Feasibility of Rice Farming Business in Semi-Technical Rice Farming Typology in Tanjung Agung District, Muara Enim Regency. The type of research used in this study is a quantitative descriptive method. The data analysis used in this study is quantitative analysis. The results of the study show that rice farmers in Tanjung Agung District, Muara Enim Regency earn income in the form of GKP with an average of Rp 13,483,038/Ha/MT and in the form of rice of Rp 29,472,432/Ha/MT. From the results of the calculation of the R/C ratio, it can be seen that the Semi-Technical Rice Typology paddy rice farming in Tanjung Agung District, Muara Enim Regency as a whole is economically feasible so that the value is more than 1 both in the form of GKP and Rice, so the Semi-Technical Paddy Typology Paddy Farm is very feasible to be continued or pursued in accordance with applicable regulations. However, the R/C ratio value of rice is higher than GKP. This is shown by the value of the R/C ratio of rice, which is 4.16, which means that every cost expenditure of Rp 100 will receive a revenue of Rp 416.